A novel band‐pass filter based on a periodically drilled SIW structure. Issue 4 (25th April 2016) - Coves, A.; Torregrosa‐Penalva, G.; San‐Blas, A. A.; Sánchez‐Soriano, M. A.; Martellosio, A.; Bronchalo, E.; Bozzi, M.
Abstract: The design and fabrication of a band‐pass step impedance filter based on high and low dielectric constant sections has been realized on substrate integrated waveguide (SIW) technology. The overall process includes the design of the ideal band‐pass prototype filter, where the implementation of the impedance inverters has been carried out by means of waveguide sections of lower permittivity. This can be practically achieved by implementing arrays of air holes along the waveguide. Several SIW structures with and without arrays of air holes have been simulated and fabricated in order to experimentally evaluate their relative permittivity. Additionally, the equivalent filter in SIW technology has been designed and optimized. Finally, a prototype of the designed filter has been fabricated and measured, showing a good agreement between measurements and simulations, which demonstrates the validity of the proposed design approach. Key Points: A band‐pass filter is demonstrated using high‐ and low‐impedance SIW sections A lower permittivity can be achieved by performing arrays of air holes along the waveguide A prototype of the designed filter has been fabricated and measured, showing a good agreement between measurements and simulations